Growth, structural, and optical characterization of ZnO-coated cellulosic fibers - Gonçalves, G.
Rod-shaped ZnO particles were grown over wood cellulose fibers using a two-step process. In the first step, the formation of ZnO seeds at cellulose fibers surfaces was induced by the alkaline hydrolysis of aqueous Zn(II); in the second step, the growth of the ZnO seeds into larger nanoparticles was promoted by the controlled hydrolysis of Zn(II)−amine complexes. In particular, we will report the use of hexamethylenetetramine (C6H12N4) and triethanolamine (C6H15NO3) to grow, respectively, ZnO nanorods and microrods at the cellulose fibers surfaces. Photoluminescence measurements performed on the nanocomposite materials showed the typical excitonic ZnO recombination peaked between 3.38 and 3.34 eV, at low temperature. The full width at half-maximum of the excitonic line is dependent on the ZnO particles morphology and can be as narrow as 30 meV for some of the materials investigated.